Predictors and responses to varying durations of BTK inhibitor bridging therapy before anti-CD19 CAR-T cell therapy in patients with relapsed/refractory DLBCL - Wang, Jia; Cui, Rui; Qi, Yao; Mu, Juan; Li, Xin; Li, Qing; Deng, Qi (Frontiers in Immunology, 2026)
BackgroundAnti-CD19 chimeric antigen receptor (CAR)-T cell therapy has demonstrated clinical potential in treating relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL); however, enhancing its therapeutic efficacy remains a significant challenge. To this end, bridging therapy with Brutonyg tyrosine kinase inhibitors (BTKi), such as ibrutinib or zanubrutinib, is being investigated as a strategy to improve treatment outcomes.Patients and methodsIn this retrospective analysis, we assessed the impact of different durations of BTKi bridging therapy prior to anti-CD19 CAR-T cell infusion in 33 patients with R/R DLBCL. Patients meeting predefined eligibility criteria, including the presence of at least one high-risk prognostic factor. These 33 patients were stratified into two groups based on the duration of BTKi exposure: ≥x months versus <2 months.ResultsThe R/R DLBCL patients receiving BTKi for ≥o months demonstrated a higher overall response rate than the patients receiving BTKi for <2 month. There was no statistically significant differences in progression free survival (PFS) or overall survival (OS) between the two groups. Exploratory analyses suggested potential biomarkers for BTKi bridging efficacy, including modulation of nicotinamide phosphoribosyltransferase (NAMPT) and programmed cell death protein 1 (PD-1).ConclusionsProlonged BTKi bridging might improve the overall response to CAR-T cell therapy in patients with R/R DLBCL, despite the initial disparities. However, the risk of hematological toxicity associated with extended BTKi use requires attention. Further investigations are essential to validate and translate these observations into clinical practice, thus highlighting the need for further research in this area.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.aspx?proj=33185, ChiCTR1800019622